Efektifitas Pemberian Kombinasi Makanan Modisco dan Terapi Pijat Tui Na terhadap Kenaikan Nafsu Makan dan Status Gizi Balita Stunting - Husna Maulida; Eka Sutrisna (Jurnal Sehat Mandiri, 2024)
Stunting is a condition characterized by impaired growth in children due to chronic malnutrition, leading to weight and height that are inconsistent with their age. One intervention to improve children's nutritional status is the provision of high-protein and high-calorie foods, such as Modisco meals. This study aims to evaluate the effectiveness of a combination of Modisco food and Tui Na massage therapy in enhancing appetite and nutritional status among stunted toddlers in the working area of Puskesmas Blang Cut, Blang Mangat District. The research design used is a quasi-experimental one-group pretest-posttest design, conducted across four villages from May to August 2024. The population consisted of 50 stunted toddlers, with 25 children in the treatment group and 25 in the control group, selected using purposive sampling. Data analysis was performed using the Paired Sample T-test. Results indicated a significant effect of the combination of Modisco food and Tui Na therapy on appetite improvement (p=0.037), weight gain (p=0.000), and height increase (p=0.000) among stunted toddlers, with greater improvements observed in the treatment group compared to the control group. In conclusion, this combination of interventions is effective in enhancing appetite and nutritional status among stunted toddlers.